If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6a + -4 = 5a + -8 Reorder the terms: -4 + 6a = 5a + -8 Reorder the terms: -4 + 6a = -8 + 5a Solving -4 + 6a = -8 + 5a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-5a' to each side of the equation. -4 + 6a + -5a = -8 + 5a + -5a Combine like terms: 6a + -5a = 1a -4 + 1a = -8 + 5a + -5a Combine like terms: 5a + -5a = 0 -4 + 1a = -8 + 0 -4 + 1a = -8 Add '4' to each side of the equation. -4 + 4 + 1a = -8 + 4 Combine like terms: -4 + 4 = 0 0 + 1a = -8 + 4 1a = -8 + 4 Combine like terms: -8 + 4 = -4 1a = -4 Divide each side by '1'. a = -4 Simplifying a = -4
| 6t+4=5t-7 | | 7xy-3y^3+2x-3xy+y^3+10x= | | -2n-(q-1on)= | | 3x-0=1 | | C(-6-c)=0 | | x^2-4x-80=0 | | 3x-26=12 | | 2.2/5=x/4 | | x/2-3/4=(5/8)x+9/4 | | 4.8/7=x/4 | | 2/3=x/4 | | 2.4/5=x/4 | | B(14+b)=0 | | t=25 | | 5.8/7=x/4 | | (4w+3v)(4w-3v)= | | (2x+3)(x-2)=2x | | 5n+3x=n | | 4(x-7)+2=-5(x-2) | | x+3y=n-1 | | 5n+3x= | | 3x-6x=9x | | 16-64=0 | | f(x)=9+1 | | f(x)=-3+1 | | 6(-70%x+6)=5*8-2x | | (3/2)x=15 | | f(x)=-2(3)-5 | | (3x-6)(2x-2)=0 | | 1/4+2x=1/5x+1 | | 75=5+3x | | (x+2)*(x+1)+(x+3)*(x+1)=2x^2+12 |